Renal Na(+)-phosphate cotransport in murine X-linked hypophosphatemic rickets. Molecular characterization. - Tenenhouse, H S (1994)
The X-linked Hyp mouse is characterized by a specific defect in proximal tubular phosphate (Pi) reabsorption that is associated with a decrease in Vmax of the high affinity Na(+)-Pi cotransport system in the renal brush border membrane. To understand the mechanism for Vmax reduction, we examined the effect of the Hyp mutation on renal expression of Na(+)-Pi cotransporter mRNA and protein. Northern hybridization of renal RNA with a rat, renal-specific Na(+)-Pi cotransporter cDNA probe (NaPi-2) (Magagnin et al. 1993. Proc. Natl. Acad. Sci. USA. 90:5979-5983.) demonstrated a reduction in a 2.6-kb transcript in kidneys of Hyp mice relative to normal littermates (NaPi-2/beta-actin mRNA = 57 +/- 6% of normal in Hyp mice, n = 6, P < 0.01). Na(+)-Pi cotransport, but not Na(+)-sulfate cotransport, was approximately 50% lower in Xenopus oocytes injected with renal mRNA extracted from Hyp mice when compared with that from normal mice. Hybrid depletion experiments documented that the mRNA-dependent expression of Na(+)-Pi cotransport in oocytes was related to NaPi-2. Western analysis demonstrated that NaPi-2 protein is also significantly reduced in brush border membranes of Hyp mice when compared to normals. The present data demonstrate that the specific reduction in renal Na(+)-Pi cotransport in brush border membranes of Hyp mice can be ascribed to a proportionate decrease in the abundance of Na(+)-Pi cotransporter mRNA and protein.